Association of Mushroom Cultivation and Ozonolysis as Pretreatment for Enzymatic Saccharification of Sengon(Falcataria moluccana) Sawdust - Denny Irawati; Soekmana Wedatama; Futoshi Ishiguri; Shinso Yokota (Jurnal Ilmu Kehutanan)
Wood industry based on sengon (Falcataria moluccana) material has developed rapidly and cause the huge wastes. Lignocellulosic materials, such as sengon sawdust, offer a great potential as cheap and abundant feedstock for biofuels production. Ozone oxidation pretreatment was carried out on sengon wastes to improve fermentable sugar production by enzymatic saccharification. Sengon wood (SW), sengon media (SM), and sengon spent media (SMM), that was waste of media after mushroom cultivation, treated with ozone for different treatment time were enzymatically saccharified. Then the decrease of hydrolysis weight, reducing sugar yield, and monosaccharide yields were determined. Ozone treatment resulted in Klason lignin degradation in the all samples, resulting in the improvement of subsequent enzymatic saccharification. Ozone treatment with the duration more than 30 min was not suitable for SMM sample. Glucose yield after saccharification from the ozone-treated sample for 60 min was the highest among all samples in SW and SM treated, but for SMM it was 30 min. Based on these results, we concluded that mushroom cultivation can reduce the ozone time treatment and it is an effective treatment to improve sugar yield by enzymatic saccharification of sengon wastes.